Quercetin improves and protects Calu-3 airway epithelial barrier function - DiGuilio, K. M.; Rybakovsky, E.; Valenzano, M. C.; Nguyen, H. H.; Del Rio, E. A.; Newberry, E.; Spadea, R.; Mullin, J. M. (Frontiers in Cell and Developmental Biology, 2023)
In light of the impact of airway barrier leak in COVID-19, and the significance of Vitamin D in COVID-19 outcomes as well as airway barrier protection specifically, we asked whether the very common dietary flavonoid, quercetin, could also be efficacious in supporting airway barrier function. Toward this end we utilized the widely used airway epithelial cell culture model, Calu-3. We observed that treating Calu-3 cell layers with quercetin increased transepithelial electrical resistance (TER) and simultaneously reduced transepithelial leak of 14C-D-mannitol (Jm) as well as 14C-inulin. Quercetin’s action was concentration dependent and had a biphasic time course. These effects of quercetin occurred with changes in tight junctional protein composition, but also a partial inhibition of cell replication that resulted in decreased linear junctional density, both effects potentially contributing to improved barrier function. Quercetin was equally effective in reducing the barrier compromise caused by the proinflammatory cytokine, TNF-α, an action that seemingly derived in part from reducing the elevation of ERK 1/2 caused by TNF-α.